Phosphorous Removal Potential of Vertical Constructed Wetlands Filled with Different Filter Materials - Minakshi, Deepa; Sharma, Pradeep Kumar; Rani, Anju; Malaviya, Piyush (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940343);" role="presentation">This investigation <span dir="ltr" style="left: calc(var(--scale-factor)*147.50px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919555);" role="presentation">was carried out to observe the effec<span dir="ltr" style="left: calc(var(--scale-factor)*292.73px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958114);" role="presentation">ts of filter materials <span dir="ltr" style="left: calc(var(--scale-factor)*375.91px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922181);" role="presentation">on contaminant removal <span dir="ltr" style="left: calc(var(--scale-factor)*477.22px); top: calc(var(--scale-factor)*367.49px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938784);" role="presentation">efficiencies <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00439);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*84.14px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0016);" role="presentation">Vertic<span dir="ltr" style="left: calc(var(--scale-factor)*109.10px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927886);" role="presentation">al <span dir="ltr" style="left: calc(var(--scale-factor)*120.26px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950526);" role="presentation">Constructed Wetland (V<span dir="ltr" style="left: calc(var(--scale-factor)*220.73px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976864);" role="presentation">CW) units. <span dir="ltr" style="left: calc(var(--scale-factor)*269.81px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971262);" role="presentation">Nine real scale V<span dir="ltr" style="left: calc(var(--scale-factor)*343.03px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964781);" role="presentation">CW <span dir="ltr" style="left: calc(var(--scale-factor)*363.07px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920259);" role="presentation">units <span dir="ltr" style="left: calc(var(--scale-factor)*386.47px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.893586);" role="presentation">were <span dir="ltr" style="left: calc(var(--scale-factor)*409.63px); top: calc(var(--scale-factor)*380.69px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.967841);" role="presentation">operated for a period of 12 <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.886444);" role="presentation">months (Jan - <span dir="ltr" style="left: calc(var(--scale-factor)*129.14px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916684);" role="presentation">Dec 2016) <span dir="ltr" style="left: calc(var(--scale-factor)*174.02px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919115);" role="presentation">for treating dairy wastewater. <span dir="ltr" style="left: calc(var(--scale-factor)*294.53px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990816);" role="presentation">All nine V<span dir="ltr" style="left: calc(var(--scale-factor)*336.79px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964781);" role="presentation">CW <span dir="ltr" style="left: calc(var(--scale-factor)*355.51px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955318);" role="presentation">units were filled with d<span dir="ltr" style="left: calc(var(--scale-factor)*448.78px); top: calc(var(--scale-factor)*393.89px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955464);" role="presentation">ifferent sized filter <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903326);" role="presentation">materials <span dir="ltr" style="left: calc(var(--scale-factor)*111.26px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891342);" role="presentation">(gravels and sand) <span dir="ltr" style="left: calc(var(--scale-factor)*187.61px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869552);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*204.89px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927262);" role="presentation">were planted with <span dir="ltr" style="left: calc(var(--scale-factor)*279.41px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934603);" role="presentation">Arundo <span dir="ltr" style="left: calc(var(--scale-factor)*312.17px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905757);" role="presentation">donax <span dir="ltr" style="left: calc(var(--scale-factor)*339.43px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891079);" role="presentation">at surface. The <span dir="ltr" style="left: calc(var(--scale-factor)*401.47px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946525);" role="presentation">hydraulic <span dir="ltr" style="left: calc(var(--scale-factor)*441.94px); top: calc(var(--scale-factor)*407.84px); font-size: calc(var(--scale-factor)*9.00px); font-family: sans-serif; transform: scaleX(0.954643);" role="presentation">retention <span dir="ltr" style="left: calc(var(--scale-factor)*476.50px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.929847);" role="presentation">time <span dir="ltr" style="left: calc(var(--scale-factor)*496.66px); top: calc(var(--scale-factor)*407.11px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">(HRT) <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05195);" role="presentation">for all the units was <span dir="ltr" style="left: calc(var(--scale-factor)*167.18px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.992228);" role="presentation">fixed as <span dir="ltr" style="left: calc(var(--scale-factor)*206.57px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02611);" role="presentation">24 h. <span dir="ltr" style="left: calc(var(--scale-factor)*234.65px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.983117);" role="presentation">The major <span dir="ltr" style="left: calc(var(--scale-factor)*284.21px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89869);" role="presentation">water <span dir="ltr" style="left: calc(var(--scale-factor)*311.57px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.975283);" role="presentation">parameter focused in the present study was <span dir="ltr" style="left: calc(var(--scale-factor)*505.54px); top: calc(var(--scale-factor)*420.43px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942577);" role="presentation">total <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884988);" role="presentation">phosphorous (T<span dir="ltr" style="left: calc(var(--scale-factor)*135.86px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887213);" role="presentation">P). <span dir="ltr" style="left: calc(var(--scale-factor)*150.38px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.941204);" role="presentation">The findings of this study revealed that all the three <span dir="ltr" style="left: calc(var(--scale-factor)*366.07px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.02934);" role="presentation">filter <span dir="ltr" style="left: calc(var(--scale-factor)*388.87px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.892839);" role="presentation">media <span dir="ltr" style="left: calc(var(--scale-factor)*416.35px); top: calc(var(--scale-factor)*433.63px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.959661);" role="presentation">(10 mm & 20 mm gravels <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.870573);" role="presentation">and sand) <span dir="ltr" style="left: calc(var(--scale-factor)*113.42px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94442);" role="presentation">were efficient in removing <span dir="ltr" style="left: calc(var(--scale-factor)*222.65px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902279);" role="presentation">phosphorus fro<span dir="ltr" style="left: calc(var(--scale-factor)*283.13px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917705);" role="presentation">m dairy wastewater. <span dir="ltr" style="left: calc(var(--scale-factor)*366.67px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(--scale-factor)*384.91px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.859327);" role="presentation">average <span dir="ltr" style="left: calc(var(--scale-factor)*418.51px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922659);" role="presentation">concentration of T<span dir="ltr" style="left: calc(var(--scale-factor)*492.82px); top: calc(var(--scale-factor)*446.83px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.90784);" role="presentation">P in the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934306);" role="presentation">dairy influent was recorded as 39.3 <span dir="ltr" style="left: calc(var(--scale-factor)*219.89px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.990915);" role="presentation">± 9.8 mg L-1. <span dir="ltr" style="left: calc(var(--scale-factor)*277.73px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91264);" role="presentation">Average T<span dir="ltr" style="left: calc(var(--scale-factor)*321.07px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.947301);" role="presentation">P concentration in gravel filters <span dir="ltr" style="left: calc(var(--scale-factor)*453.58px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971988);" role="presentation">(CW-<span dir="ltr" style="left: calc(var(--scale-factor)*476.26px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.970231);" role="presentation">1 to <span dir="ltr" style="left: calc(var(--scale-factor)*495.82px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964573);" role="presentation">CW-<span dir="ltr" style="left: calc(var(--scale-factor)*515.14px); top: calc(var(--scale-factor)*460.03px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.942041);" role="presentation">6) <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910157);" role="presentation">were recorded in the range of 16.9 to 18.1 mg L-1 <span dir="ltr" style="left: calc(var(--scale-factor)*271.85px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.940489);" role="presentation">while in sand filters <span dir="ltr" style="left: calc(var(--scale-factor)*353.59px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.971988);" role="presentation">(CW-7 <span dir="ltr" style="left: calc(var(--scale-factor)*383.83px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931408);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*394.27px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.964573);" role="presentation">CW-<span dir="ltr" style="left: calc(var(--scale-factor)*413.59px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943192);" role="presentation">9), <span dir="ltr" style="left: calc(var(--scale-factor)*427.03px); top: calc(var(--scale-factor)*473.23px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.900872);" role="presentation">it ranged between 2.2 to <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.951043);" role="presentation">3.9 mg L-1. <span dir="ltr" style="left: calc(var(--scale-factor)*119.54px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931742);" role="presentation">The r<span dir="ltr" style="left: calc(var(--scale-factor)*141.26px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.915336);" role="presentation">eduction <span dir="ltr" style="left: calc(var(--scale-factor)*178.46px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01877);" role="presentation">of TP <span dir="ltr" style="left: calc(var(--scale-factor)*204.29px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946734);" role="presentation">in the effluent <span dir="ltr" style="left: calc(var(--scale-factor)*263.69px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.875648);" role="presentation">was <span dir="ltr" style="left: calc(var(--scale-factor)*282.05px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924575);" role="presentation">more in case of sand filters (2.2 ± 2.6 <span dir="ltr" style="left: calc(var(--scale-factor)*436.75px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.972618);" role="presentation">mg L-1<span dir="ltr" style="left: calc(var(--scale-factor)*463.66px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958384);" role="presentation">). <span dir="ltr" style="left: calc(var(--scale-factor)*472.30px); top: calc(var(--scale-factor)*486.55px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922595);" role="presentation">The removal <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*499.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.921384);" role="presentation">rate in sand filters showed <span dir="ltr" style="left: calc(var(--scale-factor)*181.82px); top: calc(var(--scale-factor)*499.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922861);" role="presentation">noticeable reduction as compared to gravel filters. M<span dir="ltr" style="left: calc(var(--scale-factor)*396.79px); top: calc(var(--scale-factor)*499.75px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93592);" role="presentation">aximum removal rate of 94.1% <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*512.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91781);" role="presentation">was also observed in sand filled units <span dir="ltr" style="left: calc(var(--scale-factor)*226.01px); top: calc(var(--scale-factor)*512.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92644);" role="presentation">while minimum removal was seen in gravel beds (<span dir="ltr" style="left: calc(var(--scale-factor)*429.91px); top: calc(var(--scale-factor)*512.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.92452);" role="presentation">54.7 to 58.1%). <span dir="ltr" style="left: calc(var(--scale-factor)*495.34px); top: calc(var(--scale-factor)*512.95px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884913);" role="presentation">Hence, t<span dir="ltr" style="left: calc(var(--scale-factor)*74.78px); top: calc(var(--scale-factor)*526.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95304);" role="presentation">he results of this investigation recom<span dir="ltr" style="left: calc(var(--scale-factor)*228.53px); top: calc(var(--scale-factor)*526.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933891);" role="presentation">mends the use of sand as t<span dir="ltr" style="left: calc(var(--scale-factor)*340.51px); top: calc(var(--scale-factor)*526.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903312);" role="presentation">he bet<span dir="ltr" style="left: calc(var(--scale-factor)*365.83px); top: calc(var(--scale-factor)*526.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.903508);" role="presentation">ter o<span dir="ltr" style="left: calc(var(--scale-factor)*385.15px); top: calc(var(--scale-factor)*526.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.99766);" role="presentation">ption for T<span dir="ltr" style="left: calc(var(--scale-factor)*431.11px); top: calc(var(--scale-factor)*526.15px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.943579);" role="presentation">P removal and a good <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*539.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898588);" role="presentation">alternate <span dir="ltr" style="left: calc(var(--scale-factor)*108.86px); top: calc(var(--scale-factor)*539.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94294);" role="presentation">for designing V<span dir="ltr" style="left: calc(var(--scale-factor)*171.62px); top: calc(var(--scale-factor)*539.35px); font-size: calc(var(--scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931602);" role="presentation">CW in future wetland construction